2021
DOI: 10.1093/rb/rbab059
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of rose bengal and green light crosslinked collagen scaffolds for regenerative medicine

Abstract: Collagen is one of the most important biomaterials for tissue engineering approaches. Despite its excellent biocompatibility, it shows the non-negligible disadvantage of poor mechanical stability. Photochemical crosslinking with rose bengal and green light (RGX) is an appropriate method to improve this property. The development of collagen laminates is helpful for further adjustment of the mechanical properties as well as the controlled release of incorporated substances. In this study, we investigate the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The swelling degree of the collagen laminates and the single RGX-modified collagen sheets was determined by a method reported previously by Eckes et al and Braun et al [ 15 , 17 ]. In brief, the collagen samples were prepared, as described in Section 2.1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The swelling degree of the collagen laminates and the single RGX-modified collagen sheets was determined by a method reported previously by Eckes et al and Braun et al [ 15 , 17 ]. In brief, the collagen samples were prepared, as described in Section 2.1 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it can stimulate bone recovery by promoting the proliferation and differentiation of mesenchymal stem cells [ 13 , 14 ]. In previous studies, we assembled commercially available collagen sheets to collagen laminates by the photochemical crosslinking with rose bengal (RB) and green light (RGX) [ 15 , 16 , 17 ]. This convenient and inexpensive method has already been used for different clinical applications [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…RB is a hydrophilic xanthene dye that has functional groups like -OH and -CO2H. RB is often used in the medical field [26]. Kurosu et al reported on the antibacterial therapeutic activity of RB dye [27].…”
Section: Introductionmentioning
confidence: 99%